Arabic Textbooks Theory Review by Muhammad Ali Al-Khuli l Al-Kutub al-Madrasiyyah al-‘Arabiyyah Bina’an ‘Ala Nadzariyyah Muhammad ‘Aly al-Khuli - Hidayah, Ni'matul; Syahrir, Sultan; Kesuma, Guntur Cahya; Puspitaningrum, Yuliani Tri (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Textbooks writing must consider the theories put forward by experts who are competent in their field. In this study, the researcher examined textbooks for Islamic junior high school (Madrasah Tsanawiyyah) with guidelines of the research on the theory put forward by Muhammad Ali Al-Khuli. The purpose of this study was to find out whether the mufrodat and tarkib material presented in textbooks was in accordance with the theory presented by Muhammad Ali Al-Khuli. This type of research was library research. The data sources were textbooks and supporting sources such as books, articles, and documents related to the research. Meanwhile, content analysis was used in analyzing the data. Based on the results of the study, it was found that there were still presentations of mufrodat and tarkib that were not in accordance with the theory of linguists. This could affect the process of acquiring a second language for students. If the presentation of the material were not in accordance with the expert's explanation, the acceptance of the material would be less than optimal. It was expected that there would be improvements to the books that are already in circulation. For the printing of the next edition, the editor would be expected to check thoroughly before the book is printed and distributed.